Fatores relacionados ao atraso no diagnóstico da hanseníase na atenção primária à saúde em um município hiperendêmico da região nordeste do brasil - Amaral, Vitória Ferreira do (2023)
Leprosy is an infectious disease, with a chronic course, with the potential to cause progressive and permanent damage, when the diagnosis and treatment are not carried out in a timely manner. This disease has a cure and free treatment through the Unified Health System, however, despite the advances in its control, the disease continues to be a challenge for some countries, such as Brazil. Of the 17,979 new cases reported in Brazil in 2020, 8.3% (1,504 cases) had grade II physical disability at the time of diagnosis, which indicates the need to improve the safety of services offered by SUS. The objective of this study is to highlight the factors that do not contribute to the safety of patients with leprosy in primary health care, in a hyperendemic municipality in the northeast region of Brazil. This is an epidemiological, cross-sectional, descriptive study, with a quantitative approach, carried out in the municipality of Sobral-Ceará, from August 2022 to March 2023, based on the records of leprosy cases in the Sistema de Información de Enfermedades de Obligatory Declaration, referring to the period from 2016 to 2020. The population chosen to compose it was: ocho affected by leprosy with degree of physical disability of the; veintisiete enfermeros y nueve Médicos de laEstrategia de Salud de la Familia del municipality. The operationalization of this study's collection was carried out through the local database of the Obligatory Declaration Disease Information System and the Electronic Clinical History System, and from the application of two questionnaires and semi-structured interview instruments. The collected quantitative data were analyzed using the Statistical Package for Social Sciences software, version 23.0® by IBM®, using Pearson's Chi-square association statistical test, with a significance level of 5%. While the qualitative data were explored through Bardin's content analysis, which allowed to identify that the main mode of diagnosis of leprosy is by spontaneous demand. The municipality does not have an institutional flow for the diagnosis of leprosy. For professionals, the main limitations of the service for late diagnosis are: the high demand for attention, the user itself, the absence of monofilaments, weaknesses in the provision of information and the lack of ease of diagnosis; and the potentialities are: the professionals themselves, the Reference Center for Infectious Diseases of Sobral, the provision of permanent education and medication. For the people affected by leprosy, what contributed to the delay in the diagnosis was the lack of knowledge of professionals about leprosy, while the contributions to making the diagnosis were the search for attention. Thus, the results shown indicate the need for active detection, for the early diagnosis of new cases of leprosy in time. In addition, the results could enable the direction of strategies that favor the diagnosis in atimely manner, with safety and quality. This project was approved by Plataforma Brasil, under the decree number 64623422.9.0000.8133.